Fontanes Medien - Trilcke, Peer (De Gruyter, 2022)
This volume views the rapid mediatization of society in the nineteenth century as a productive framework for the "media worker" Theodor Fontane. Embedded within a ramified network of postal text circulation, familiar with the popular periodical press, for which he would write throughout his life, and shaped in various ways by the visual culture of his time, this volume demonstrates that Fontane was a journalistic and aesthetic crossover artist.